Sculture nel verde. Le prime esposizioni all’aperto di scultura contemporanea: le esperienze italiane in relazione alla scena europea (1948 – 1957) - Paola Torre (Annali Online dell'Università di Ferrara. Sezione Lettere)
This contribution focuses on the analysis of the origin and diffusion of the open air sculpture exhibitions, in Europe and in Italy. The article intends to explain how and where this particular type of exposition was born and in which way it changed the museologists’ and artists’ approach to the organization of sculpture exhibitions. In this sense, it contributed to create a new connection between sculptures and nature, not only intended in its concept of “space”, but also of “place”. The London exposition in Battersea Park in 1948 can be considered the first example of open air sculpture exhibition; it became a model for the successive exhibitions as Sonsbeek ‘49 in Arnhem and Exposition internationale en plein air de sculpture 1900-1950 in the Middelheim Park of Antwerp. At the same time, the diffusion of the open air sculpture exhibitions took place in Italy; in 1949 and in 1953 two major exposition of international contemporary sculpture have been organized in Villa Mirabello’s gardens in Varese. In 1957, another important open air sculpture exhibition — completely dedicated to the Italian contemporary sculpture — was organized in Villa Mazzini’s garden, in Messina.